The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.28940/terra.v38i4.603
|View full text |Cite
|
Sign up to set email alerts
|

The potential of Mimosa pigra to restore contaminated soil with anthracene and phenanthrene

Abstract: Hydrocarbon contamination cause serious environmental damage and human health problems, therefore, to resolve this problem has been proposed diversely remediation techniques friendly with the environment i.e. bioaugmentation, biostimulation, natural attenuation and phytoremediation. Among options, the phytoremediation causes minimum alterations to soil, low cost, it has proved good eff iciency and gained public acceptation. In the present study, the capacity of Mimosa pigra to restore a contaminated soil with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 79 publications
(104 reference statements)
0
1
0
Order By: Relevance
“… 2019 ; Pérez-Hernández et al. 2020 ). These studies revealed both the benefits and disadvantages of M. pigra ; however, genomic and proteomic researches are required.…”
mentioning
confidence: 99%
“… 2019 ; Pérez-Hernández et al. 2020 ). These studies revealed both the benefits and disadvantages of M. pigra ; however, genomic and proteomic researches are required.…”
mentioning
confidence: 99%